PERENCANAAN KOMUNIKASI DALAM MEMBENTUK PROGRAM KELOMPOK INFORMASI MASYARAKAT (KIM) OLEH DINAS KOMUNIKASI DAN INFORMATIAK KABUPATEN INDRAGIRI HULU - Ayu Erlina; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Public information at this time is the main requirement for everyone, in addition to the need for clothing, food and shelter. Public information occurs on the basis of communication between individuals one and the other individual. Meanwhile public information disclosure will move the community to play an active role and participate in the implementation of development in their region, so that development is truly related and for the benefit of the people. However, it is not easy for the community to access public information relating to the community, because in reality not all communities in Indragiri Hulu Regency can receive information well because of limited access to public information and low levels of knowledge in terms of technology. These problems bring the government to be able to develop information networks in their regions through the establishment of social communication institutions, namely the Community Information Group. This study aims to find out the process carried out in implementing this community information group program. This research was conducted with a descriptive qualitative approach. Research subjects were determined based on a purposive technique consisting of the Head of Communication and Information Services, Head of Information and Public Communication, secretaries, Head of Human Resources Management and General Functional Staff, and 3 people who had joined the KIM program. Data collection techniques include interviews, observation, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion drawing. Data validity checking techniques include the extension of participation and triangulation. The results showed that Diskominfo Inhu's communication planning in forming the KIM program was based on four basic KIM programs, which were seen from the condition of society, region, information and institutions. This program was formed based on policies from the Minister of Communication and Information and Decree of the Governor of Riau. In the selection of targets for dissemination activities Diskominfo Inhu chose the target was the general public of Indragiri Hulu. The message conveyed in the socialization activities using informative, persuasive sentences. The media used are young face communication media and internet media. Feedback from diverse communities is accepted by the program and some are not. The evaluation activities carried out by Diskominfo are still not effective because of the many obstacles in the process of implementing this community information group program. In group communication conducted by KIM Sedhoyo all democratic systems such as, the election of a chairperson, decision making, resolving conflicts. KIM Sedhoyo has a written norm to regulate the behavior of each group member